e-Learning in education - Garner, Simon; Rogers, Christine; Video Education Australasia (Australia : Video Education Australasia, 2008)
This program is about encouraging and inspiring teachers to incorporate e-learning as an integral part of the curriculum. It looks at a revolution in youth communication; the implications of the revolution for education : multilliteraces, recent developments such as podcasts, vodcasts, mobiles, PDA's blogs and online learning; and the way forward
Executive producer, Simon GArner ; camera, Peter Zacharov, Max Davis
Voice over: Lisa Hickey
DVD format
Keywords: Internet in education; Educational innovations; Podcasting